La distancia que nos une. Distancia y soledad en el mundo digital hiperconectado (2022)
The videosphere in which the world consists is actually a videocracy, a system of control and domination that through the digital information obtained about us puts an end to our freedom. The cause of this phenomenon is our desire for security. The democracy of freedom has been surpassed by the democracy of security, by cyberdemocracy. Today everything is at a distance, including the human community. Paradoxically, distance is the only thing that unites us today. Today’s community can only be made up of connected loneliness.